Clinical Efficacy of Complex Treatment of Chronic Adenoiditis Using Phototherapy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In the period from 2021 to 2022, we examined 70 children who applied to the Bukhara Regional Children's Multidisciplinary Medical Center ENT department. The age distribution was as follows: children of the first year (7 months to 11 months) – 2 (3%), early age (from 1 to 2 years) – 16 (22.8%), preschool (3 l – 6 years) - 33 (47.2%) and school age (7 l – 11 years old) – 19 (27.3%) children. Patients of preschool age (from 3 to 6 years, 47.2%) prevailed among the patients.The use of the method of complex low-frequency ultrasound therapy of chronic adenoiditis with rhinosinusitis in children reduces the duration of treatment by 40%, increases its effectiveness by 4 times and increases the proportion of recoveries 3 times for immediate and 4 times for long-term results compared with traditional treatment.